The Effectiveness of Qanun Jinayat in Preventing Sexual Violence Against Children from a Psychological Perspective - Zuriah Zuriah; Teuku Amnar Saputra; Muhammad Novriansyah (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
The Ministry of Women's Empowerment and Child Protection (PPPA) noted that 45% of the 14,571 cases of violence against children were cases of sexual violence. In Aceh, the UPTD-PPA noted that during 2021 there were 697 cases of sexual violence against women and children. The impact on victims of sexual violence can be said to be very heavy and prolonged. So far, the settlement of cases of violence against children, especially in Aceh, refers to the implementation of Aceh Qanun 6 of 2014 concerning the Jinayat Law. When compared with the loss of the victim, the punishment of Ta'zir Whip is still considered unable to provide a deterrent effect to the perpetrators. Therefore, this study aims to examine the effectiveness of the Qanun Jinayat in preventing cases of sexual violence against children. Overall, the Qanun Jinayat has not been able to provide psychological protection and recovery for victims of violence, especially children as victims. Apart from not being able to provide a deterrent effect to the perpetrators, the release of the perpetrators after the sentence creates further psychological trauma to victims of sexual violence.